Nanofibrous scaffolds for the guidance of stem cell-derived neurons for auditory nerve regeneration - Hackelberg, Sandra; Tuck, Samuel J.; He, Long; Rastogi, Arjun; White, Christina; Liu, Liqian; Prieskorn, Diane M.; Miller, Ryan J.; Chan, Che; Loomis, Benjamin R.; Corey, Joseph M.; Miller, Josef M.; et al. (PloS one, 2017)
Impairment of spiral ganglion neurons (SGNs) of the auditory nerve is a major cause for hearing loss occurring independently or in addition to sensory hair cell damage. Unfortunately, mammalian SGNs lack the potential for autonomous regeneration. Stem cell based therapy is a promising approach for auditory nerve regeneration, but proper integration of exogenous cells into the auditory circuit remains a fundamental challenge. Here, we present novel nanofibrous scaffolds designed to guide the integration of human stem cell-derived neurons in the internal auditory meatus (IAM), the foramen allowing passage of the spiral ganglion to the auditory brainstem. Human embryonic stem cells (hESC) were differentiated into neural precursor cells (NPCs) and seeded onto aligned nanofiber mats. The NPCs terminally differentiated into glutamatergic neurons with high efficiency, and neurite projections aligned with nanofibers in vitro. Scaffolds were assembled by seeding GFP-labeled NPCs on nanofibers integrated in a polymer sheath. Biocompatibility and functionality of the NPC-seeded scaffolds were evaluated in vivo in deafened guinea pigs (Cavia porcellus). To this end, we established an ouabain-based deafening procedure that depleted an average 72% of SGNs from apex to base of the cochleae and caused profound hearing loss. Further, we developed a surgical procedure to implant seeded scaffolds directly into the guinea pig IAM. No evidence of an inflammatory response was observed, but post-surgery tissue repair appeared to be facilitated by infiltrating Schwann cells. While NPC survival was found to be poor, both subjects implanted with NPC-seeded and cell-free control scaffolds showed partial recovery of electrically-evoked auditory brainstem thresholds. Thus, while future studies must address cell survival, nanofibrous scaffolds pose a promising strategy for auditory nerve regeneration.